Fecundity, an overlooked life-history trait for coastal management of commercial molluscs? - Vasconcelos, Joana; Sousa, Ricardo; Ferro, João; Pinto, Ana Rita; Freitas, Mafalda; Riera, Rodrigo (Frontiers in Marine Science, 2023)
Gonadal development in limpets is well-known. However, the integration of fecundity data on coastal management actions remains overlooked. Here, we use fecundity of two exploited limpets (Patella ordinaria and P. aspera) to demonstrate its potential as a conservation tool to preserve the harvested populations of both species. From October 2021 to June 2022, 158 females of P. ordinaria and 70 of P. aspera were collected from the coastal rocky shores of the archipelago of Madeira (NE Atlantic Ocean). The fecundity in both species appears to be determinate, and estimated batch fecundity 365,638 ± 204,462 oocytes for P. ordinaria and 73,029 ± 43,496 oocytes for P. aspera. The presence of spawning individuals of both species until May is of significant relevance to their management and conservation. A harvest-ban (November-March) is currently implemented in the coastal governance actions of P. ordinaria and P. aspera. Based on the fecundity results, small adjustments can be made to further improve the conservation of adult individuals, which are important for the continuity of future generations. So far, fecundity data constitute an overlooked life trait of key importance to preserve populations of exploited species, primarily those with limited mobility such as semi-sessile littoral limpets.